Fabrication of Anti-reflecting Si Nano-structures with Low Aspect Ratio by Nano-sphere Lithography Technique - Sun, Shenghua; Lu, Peng; Xu, Jun; Xu, Ling; Chen, Kunji; Wang, Qimin; Zuo, Yuhua (Nano-Micro Letters, 2013)
Nano-structured photon management is currently an interesting topic since it can enhance the optical absorption and reduce the surface reflection which will improve the performance of many kinds of optoelectronic devices, such as Si-based solar cells and light emitting diodes. Here, we report the fabrication of periodically nano-patterned Si structures by using polystyrene nano-sphere lithography technique. By changing the diameter of nano-spheres and the dry etching parameters, such as etching time and etching power, the morphologies of formed Si nano-structures can be well controlled as revealed by atomic force microscopy. A good broadband antireflection property has been achieved for the formed periodically nano-patterned Si structures though they have the low aspect ratio (<0.53). The reflection can be significantly reduced compared with that of flat Si substrate in a wavelength range from 400 nm to 1200 nm. The weighted mean reflection under the AM1.5 solar spectrum irradiation can be as low as 3.92% and the corresponding optical absorption is significantly improved, which indicates that the present Si periodic nano-structures can be used in Si-based thin film solar cells.